Computed Tomographic Evaluation of Intracranial Haemorrhage in Patients with Road Traffic Injuries - Dambar Sah,; Akhilesh Kumar Jha,; Mohammad Kalim Akhtar,; Mohammad Kamaluddin Rain,; Rajan Kumar Mahato,; Rajesh Acharya,; Madhu Kumari Sah,; Lokmani Upreti, (Janaki Medical College Journal of Medical Science, 2025)
Background and Objectives: Road traffic accidents (RTAs) are a major global public health concern, accounting for approximately 1.35 million deaths worldwide and representing the leading cause of mortality among children and young adults aged 5–29 years. In Nepal, RTAs are among the leading causes of death and early mortality. This study aimed to evaluate head injury patterns in RTA patients using computed tomography (CT) of the head and to determine the frequency and types of traumatic intracranial hemorrhage, including associated skull fractures.Materials and Methods: A hospital-based cross-sectional study was conducted over six months from 1st September 2024 to 29th February 2025 at the Department of Radiology, National Medical College and Teaching Hospital, Birgunj, Nepal. A total of 100 patients with a history of road traffic accidents who underwent CT head examination were included. Patients with non-traumatic causes of intracranial hemorrhage were excluded. CT imaging was performed using a 160-slice Canon CT scanner. Data were analyzed using SPSS version 26. Ethical clearance was obtained, and informed written consent was taken from all participants.Results: Among the 100 patients, 68% were male and 32% were female, with a mean age of 33.19 ± 13.15 years (range: 16–67 years). The most affected age group was 16–30 years (51%), followed by 31–45 years (33%). RTAs occurred most frequently during the evening hours (53%). Two-wheeler accidents were more common (78%) than four-wheeler accidents (22%). Skull fractures were identified in 31% of patients. Traumatic brain hemorrhage was detected in 44% of cases, including hemorrhagic contusions in 8% and extra-axial hemorrhage in 36%. Among extra-axial hemorrhages, extradural hemorrhage (EDH) was most common (18%), followed by subdural hemorrhage (SDH) (11%) and subarachnoid hemorrhage (SAH) (7%).Conclusions: The majority of the respondent had high involvement of their husband in antenatal care, but involvement in birth preparedness and complication readiness was quite low; therefore, awareness program on birth preparedness and complication readiness is recommended.